'Throwing Mud' on Questions of Sovereignty: Race and Northern Arguments over White, Chinese, and Aboriginal Labour, 1905–12. Issue 4 (2nd October 2022) - Silverstein, Ben
Abstract : This article addresses two arguments about Chinese settlers in the Northern Territory. The first, in 1905, was sparked by criticisms of Chinese mining practices and accusations that Chinese people contaminated those Aboriginal people with whom they came into contact. The second was prompted by the imposition, in 1910–11, of restrictions on Chinese rights to work and employ in the Territory. Both were opposed by the Chinese, who represented themselves as deserving and indispensable settlers who had made their home in the Northern Territory. The article argues that these arguments demonstrate the centrality of Aboriginal people to settler practices of being and belonging. Placing Indigeneity and migration in uneasy relation, it examines the emergence of racialised modes of representation as ways of both producing and obscuring sovereignties.